Effect of Conservation Measures on Runoff, Soil Loss Ground Water Recharge and Crop Productivity in Watershed - Gaur, K.P.; Mal, B.C.; Pawade, M.N.; Pendke, MS (Journal of Soil and Water Conservation, 2022)
An Area of 564 hectares was treated with various conservation measures such as contour and staggered trenches. Nala bunds, Cement plug, loose boulder darns. Contour bunds, graded bunds, Nala training works, diversion drains, afforestation and pasture developments etc., at Waganvadi, in Taluka Aundha (Nagnath), District Parbhani (M.S.) in the Catchment of Puma river, a tributary of river Godavari. Relationship between rainfall intensity-duration-return period was developed for designing different soil conservation structures. The rainfall data were analysed for erosion_index values, onset of effective monsoon and critical dry spells for agricultural management and planning. Runoff and sediment loss from the watershed during the year 1992 and 1993 were 237.69 and 200.07 mm, and 1856 and 1344 tonnes (3.3 and 2.38 t/ha/yr), respectively. Water balance model was developed considering daily measurements of rainfall and pan evaporation data over 11 year period. Groundwater flow model was also developed using finite differences technique on a nested square meshes approach. The underground water recharge was signficantly improved and helped in raising the water table from 0.3 m to 2.5 m in wells at different locations. The improvement in the productivity of different crops during the year 1992 and 1993 increased in the range of 3.83 to 32.46 per cent and 27.86 to 77.23 per cent with an average increase of 15.78 and 54.19 per cent over the base year, respectively